PENGENDALIAN PIUTANG PADA PT. BUANA RAYA EXPRESS DI SAMARINDA - Mardiana3, Diah Sawitri Elfreda Aplonia Lau2 (EKONOMIA, 2016)
Control is defined as an activity to determine whether the activity has been going according to plan and then the results of such monitoring may be used as the material for the company's actions make improvements. Control of the company's receivables to be done in order to minimize receivables that are stacked or doubtful. If the accounts receivable control to do so will result in substantial losses to the company.This study aims to determine control of receivables that occurred in PT. Buana Raya Express so as to minimize bad debts to the company. The analytical method used is by asking questions based on the questionnaire receivable control and observe the activities of the company directly subsequent results of the questionnaire was tested by dividing the total number of "Yes" with the total number of questions multiplied by one hundred percent, test results of the calculation of the questionnaire then grouped into a range of percentages, namely: not effective, less effective, quite effective and very effective.